Perioperative allergy. A 3-year experience - Rodrigo Collado-Chagoya; Rubén Cruz-Pantoja; Javier Hernández-Romero; Cristóbal León-Oviedo; Rosa Isela Campos-Gutiérrez; Andrea Velasco-Medina; Guillermo Velázquez-Sámano (Revista Alergia México, 2018)
Background: Perioperative hypersensitivity reactions constitute a global health problem, with an estimated incidence of 1 per 100,000 procedures and a mortality rate of 0.1 to 9 %. Main risk factors are a history of allergy to other drugs, atopy, associated psychiatric disorders and previous surgeries.